Calibration of Whole Body Counter in Diagnostic and Screening Modes. (Journal of Nuclear Technology in Applied Science, 2023)
The current study aims to calibrate the High Purity Germanium (HPGe) Whole-Body Counter. Four locations on the transfer phantom were considered to calculate the mean photo peak efficiency of the standard mixed gamma source. Photo peak efficiency of the HPGe detector at static, thyroid, diagnostic, and screening whole-body configurations for 88–1836 KeV was carried out. The minimum detectable activity values for some radionuclides such as 131I, 137Cs, and 60Co were calculated. The energy resolution of the HPGe whole-body counter for the energy range 88–1836 KeV was recorded as the mean value of 1%The effective dose for volunteers contaminated with 131I ranged from 13 µSv to 66 µSv. The efficiency for four compartments of fixed screening whole-body configuration was higher than the corresponding value at the diagnostic whole-body geometry by a factor of three. This makes the HPGe detector configuration good suitable for monitoring the low activity of internal contamination radionuclides.
Keywords: Transfer phantom; MDA; HPGe; Efficiency